SISTEM FONOLOGI BAHASA TAE (The Phonology System of Tae Language) - NFN Suparman; NFN Nurliana (Kandai, 2022)
This study aims to identify and describe qualitatively the phonological system of Tae Rongkong dialect in North Luwu Regency, South Sulawesi. The analysis was carried out on 200 Swadesh vocabularies carried out in the field. The results of the study were analyzed in four categories. The categories in question are phoneme identification, phoneme distribution, phoneme clusters and tribal patterns in the Tae Rongkong dialect. In the phoneme identification carried out by researchers in the Tae dilaek Rongkong language, 5 vowel phonemes were found, including vowel phonemes [u], [a], [e], [O], and [o], and 9 consonant phonemes. which include consonant phonemes [m], [l], [s], [r], [b], [k], [d], [t], [n] obtained. In the distribution of phonemes in Tae language dialect rongkong found 9 vowel phonemes which include vowel phonemes [a], [i], [u], [I], [e], [é], [o], [ U] and [O], each of which occupies the position of a vowel sound in the Tae Rongkong dialect. In the distribution of consonant phonemes found 15 consonant phonemes in the Tae Rongkong dialect found consonant phonemes consisting of consonant phonemes [b], [d], [g], [j], [k], [l], [ m], [n], [ŋ], [p], [r], [s], [t], [v] and [?].; also found 5  vowel phoneme clusters /ai/, /ia/, /ua/, /ei/, and /oa/; and in the consonant phoneme group found 1 consonant phoneme /ŋk/; The tribal patterns found by researchers in the Tae Rongkong dialect consist of trisyllabic patterns with monosyllabic V, polysyllabic K.V, V.K, trisyllabic K.K.KV and four-syllabic KK.K.K.V.Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan secara kualitatif sistem fonologi bahasa Tae dialek Rongkong di Kabupaten Luwu Utara, Sulawesi Selatan. Analisis dilakukan pada 200 kosakata Swadesh yang dilakukan di lapangan. Hasil penelitian dianalisis dalam empat kategori. Kategori yang dimaksud ialah identifikasi fonem, distribusi fonem, gugus fonem, dan pola persukuan dalam bahasa Tae dialek Rongkong. Pada identifikasi fonem yang dilakukan peneliti pada bahasa Tae dilaek Rongkong ditemukan 5 fonem vokal di antaranya fonem vokal [u], [a], [e], [O], dan [o] dan 9 fonem konsonan di antaranya fonem konsonan [m], [l], [s], [r], [b], [k], [d], [t], dan [n]. Pada distribusi fonem yang ada pada bahasa Tae dialek Rongkong ditemukan 9 fonem vokal di antaranya fonem vokal [a], [i], [u], [I], [e], [é], [o], [U], dan [O] yang masing-masing menempati posisi keberadaan bunyi vokal pada bahasa Tae dialek Rongkong. Pada distribusi fonem konsonan ditemukan 15 fonem konsonan dalam bahasa Tae dialek Rongkong dan ditemukan lagi fonem konsonan yang terdiri atas fonem konsonan [b], [d], [g], [j], [k], [l], [m], [n], [ŋ], [p], [r], [s], [t], [v], dan [?]; ditemukan pula 5 gugus fonem vokal /ai/, /ia/, /ua/, /ei/, dan /oa/; dan pada gugus fonem konsonan ditemukan 1 fonem konsonan /ŋk/; pola persukuan yang ditemukan peneliti dalam bahasa Tae dialek Rongkong terdiri atas pola persukuan bersuku satu V, bersuku dua K.V, V.K, bersuku tiga K.K.KV, dan bersuku empat KK.K.K.V.